Stem Cells: Current Challenges and New Directions - Turksen, Kursad. (Stem Cell Biology and Regenerative Medicine,, 2013)
This latest volume in Springer'sStem Cell Biology and Regenerative Medicine serieslooks at the state-of-the-science in stem cells, discusses thecurrent challenges, and examines thenew directions the field is taking. Dr. Turksen,Editor-in-Chief of the journalStem Cell Reviews and Reports, hasassembleda volumeof internationally-known scientists who cover topics thatareboth research and clinically oriented. The contents range from sources of stem cells throughtheir physiological role inhealth and disease, therapeutic applications in regenerative medicine and ethics and society. An initial overview and a final summary bookend the contents into a cohesive and invaluable volume.